Transformative Learning: Evolutions of the adult learning theory - Biasin, Chiara (Phronesis)

(untitled) (Université de Sherbrooke, 2018)
This paper investigates how Transformative Learning has developed as the dominant theory in adult learning and education. The goals are to analyze the progressive self-sufficiency of the Theory from its discoverer and to examine its expansion as a mainstream in the field. The hypothesis is that the massive spread of the theory of Transformative Learning is due to its appeal as a master key to transformation. This has allowed the ‘autonomous’ development from Mezirow itself and the vast diffusion to the great detriment of conceptual coherence. The research questions are: How did Transformative Learning establish itself as a theory of adult education? What characteristics are at the base of this good fortune? How did Mezirow explore and then define the theory of Transformative Learning? Is the Mezirow’s reference theory another name for the Transformative Learning Theory? The article starts with the birth of Transformative Learning and then focuses on the consolidation of some core-concepts of the theory. The diffusion of different approaches will be discussed. Finally, the international affirmation of Transformative Learning is presented with references to the European network.